Spinach production in cocopeat: effects of soil block number and the number of emitters per styrofoam box on plant growth, nitrate concentration, and antioxidant activity - Machado, Rui M A (2022)
Currently, the interest in using cocopeat or coir dust alone as a growing medium to produce leafy vegetables has increased. This research aimed to evaluate the effects of soil block number and of the number of emitters per styrofoam box on plant growth, nitrate (NO3-) concentration, and antioxidant activity in spinach (Spinacia oleracea L. 'Manatee') cultivated in cocopeat. The experiment was carried out with four treatments, 8 and 14 soil blocks (160 and 280 plants m‑2) and 4 and 8 emitters per styrofoam box. The crop was irrigated and fertigated daily with a complete nutrient solution. The yield (kg m‑2) was increased significantly with soil block number and with the number of the emitters by styrofoam box, reaching 5.4 kg m‑2 in the treatment with 14 soil blocks (280 plants m‑2) and 8 emitters. Soil block number had no effect on shoot dry weight plant‑1, leaf-blade and petiole nitrate concentration and total phenols content. The increase in the number of emitters per styrofoam box decreased leaf-blade total phenol sand leaf-blade antioxidant activity. Ferric-reducing antioxidant activity (FRAP) values in the leaf-blade treatments with four emitters ranged from 7.3 to 9.7 mg eq. trolox g‑1 FW. The leaf-blade phenols content and FRAP values were ≈8 and 9 times higher than in the petioles, respectively. These results indicate that cocopeat is a very suitable growing medium for spinach production.